Hypernatural Monitoring: A Social Rehearsal Account of Smartphone Addiction - Veissière, Samuel P. L.; Stendel, Moriah (Frontiers in Psychology, 2018)
We present a deflationary account of smartphone addiction by situating this purportedly antisocial phenomenon within the fundamentally social dispositions of our species. While we agree with contemporary critics that the hyper-connectedness and unpredictable rewards of mobile technology can modulate negative affect, we propose to place the locus of addiction on an evolutionarily older mechanism: the human need to monitor and be monitored by others. Drawing from key findings in evolutionary anthropology and the cognitive science of religion, we articulate a hypernatural monitoring model of smartphone addiction grounded in a general social rehearsal theory of human cognition. Building on recent predictive-processing views of perception and addiction in cognitive neuroscience, we describe the role of social reward anticipation and prediction errors in mediating dysfunctional smartphone use. We conclude with insights from contemplative philosophies and harm-reduction models on finding the right rituals for honoring social connections and setting intentional protocols for the consumption of social information.